(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the level of physical fitness of male and female students in class X-A of Madani Palu Integrated Model State Senior High School, as well as to analyze the differences between the two. The method used was a quantitative descriptive survey with data collection techniques through the Indonesian Physical Fitness test (TKJI), which includes 60 60-meter run, a 1200-meter run (boys) and 1000 meters (girls), vertical jump, sit up, and hanging body lift. The population in this study amounted to 91 students, consisting of 38 male students and 53 female students, and the entire population was sampled (total sampling). The results showed that the majority of students were in the moderate physical fitness category, with details: 63.3% of male students and 88.3% of female students fell into this category. This finding indicates that there is no significant difference between male and female students in terms of physical fitness level. Factors that influence this result include the limited frequency of PE lessons, lack of physical activity outside of school, and inadequate infrastructure. A sustainable exercise program and good environmental support are needed to improve students’ physical fitness.